Flash Card-Based Education on Maternal Depressive Symptoms and Breastfeeding Techniques on Postpartum Mothers’ Motivation - Sumarni Sumarni; Minarti Minarti (Jurnal Bidan Cerdas, 2025)
Background: Postpartum changes occur in the body and mind for six weeks. This study examines how flashcard-based instruction affects maternal depression and fosters breastfeeding in postpartum mothers. Methods: The method used was quantitative research using the pre-experimental research design in one group (one-group pretest-posttest). The intensity of education on maternal depression and breastfeeding techniques using flash cards was measured through a pre-test before the intervention and a post-test after education. The sample used was 62 postpartum mothers. The method of collecting data is observation and a questionnaire. Data analysis and presentation through univariate and bivariate analysis. Results: The results indicated that the majority of postpartum moms were aged 20–35 years, possessed a senior high school education, were housewives, had many previous births, and experienced a normal delivery. The motivation to breastfeed rose markedly from a modest level in the pre-test (mean 41.58) to a much greater level at the post-test (mean 88.16). The Wilcoxon test results (p = 0.001 < 0.05) validated that educating mothers about depression symptoms and nursing procedures through flashcards significantly enhanced their motivation for exclusive breastfeeding during the first 3–14 days postpartum. Conclusion: This study concludes that there is an influence of maternal depressive symptoms and breastfeeding techniques on the motivation to provide breast milk to postpartum mothers during 3-14 days. Practical application: Midwives can use flash card-based teaching in postpartum care to improve maternal understanding, minimize depression symptoms, and motivate exclusive breastfeeding, improving maternal and infant health.